Research Progress on Application of Deep Eutectic Solvents for Extraction of Mycotoxins from Food Matrices - CHEN Mengtian, YANG Tianbao, LI Qingyue, ZHANG Ping’an, SONG Lianjun, HUANG Xianqing, BU Tong, ZHANG Xiya, MAO Yexuan (Shipin Kexue)
Mycotoxins in foods are an important issue in the field of public safety, posing a potential threat to human health. Sample pretreatment for the determination of mycotoxins involves several stages of extraction, being time-consuming and consuming large amounts of highly toxic organic solvents. Therefore, developing a simple, green, efficient sample pretreatment and a sensitive analytical method for the detection of mycotoxins is a crucial means to ensuring food safety. Deep eutectic solvents (DESs) have been widely used in sample pretreatment due to their unique physicochemical properties, which have become potential alternatives to traditional organic solvents. In this review, we summarize the synthesis methods, basic characteristics and application of DESs in the extraction of mycotoxins from food matrices, hoping to provide a theoretical basis for the wide application of DESs in the extraction of mycotoxins from various food matrices.